2016
DOI: 10.5935/0004-2749.20160088
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal choroidal thickness changes after intravitreal bevacizumab therapy for central serous chorioretinopathy

Abstract: Purpose: To evaluate subfoveal choroidal thickness (SFCT ) changes after intravitreal bevacizumab (IVB) therapy for central serous chorioretinopathy (CSC) using enhanced depth imaging spectral-domain optical coherence tomography (EDI-OCT ). Methods: In this retrospective study, we assessed the medical records of patients with CSC who received IVB (IVB group) or who were observed without intervention (control group). SFCT was measured using EDI-OCT. The main outcome measure was the change in SFCT. Results: Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Although Ünlü, et al in their study on intravitreal Bevacizumab concluded that there was no statistical difference anatomically between the injected and the observation groups, they found that the vision in the observation group was markedly better than the injected group this difference from our study may be owed to two factors; the first factor is that Ünlü, et al study was retrospective and did not differentiate between acute and chronic CSCR unlike our study which was on acute cases only, and the other factor is the longer mean duration of follow up in Ünlü ,et al's study which was 12.1 ± 12.8 (range: 3 to 43) months in the injected group and 8.8 ± 9.4 (range: 3 to 40) months in the observation group while in our study all patients were followed up to 4 months (24) .…”
Section: Discussioncontrasting
confidence: 64%
“…Although Ünlü, et al in their study on intravitreal Bevacizumab concluded that there was no statistical difference anatomically between the injected and the observation groups, they found that the vision in the observation group was markedly better than the injected group this difference from our study may be owed to two factors; the first factor is that Ünlü, et al study was retrospective and did not differentiate between acute and chronic CSCR unlike our study which was on acute cases only, and the other factor is the longer mean duration of follow up in Ünlü ,et al's study which was 12.1 ± 12.8 (range: 3 to 43) months in the injected group and 8.8 ± 9.4 (range: 3 to 40) months in the observation group while in our study all patients were followed up to 4 months (24) .…”
Section: Discussioncontrasting
confidence: 64%
“…In acute CSCR, intravitreal bevacizumab injection was not superior to observation. [ 19 ] In our study, acute CSCR cases were observed without any treatment. Although not statistically significant, a decrease in SFCT was observed, similar to the literature by Unlu et al Besides, in our study, changes in CT at neighboring points were analyzed and a significant reduction was found at N1500.…”
Section: Discussionmentioning
confidence: 79%
“…The efficacy of PDT for chronic CSC has been reported previously, however [ 2 , 3 , 11 ], and it is ethically challenging to follow up on chronic CSC without treatment. In addition, since the current results are relatively large compared to choroidal changes during spontaneous remission in acute CSC [ 35 , 36 ], we believe that the choroidal changes observed in this study were related to PDT.…”
Section: Discussionmentioning
confidence: 86%